Selection by higher‐order effects of salinity and bacteria on early life‐stages of Western Baltic spring‐spawning herring. (19th April 2017) - Poirier, Maude; Listmann, Luisa; Roth, Olivia
Abstract: Habitat stratification by abiotic and biotic factors initiates divergence of populations and leads to ecological speciation. In contrast to fully marine waters, the Baltic Sea is stratified by a salinity gradient that strongly affects fish physiology, distribution, diversity and virulence of important marine pathogens. Animals thus face the challenge to simultaneously adapt to the concurrent salinity and cope with the selection imposed by the changing pathogenic virulence. Western Baltic spring‐spawning herring ( Clupea harengus ) migrate to spawning grounds characterized by different salinities to which herring are supposedly adapted. We hypothesized that herring populations do not only have to cope with different salinity levels but that they are simultaneously exposed to higher‐order effects that accompany the shifts in salinity, that is induced pathogenicity of Vibrio bacteria in lower saline waters. To experimentally evaluate this, adults of two populations were caught in their spawning grounds and fully reciprocally crossed within and between populations. Larvae were reared at three salinity levels, representing the spawning ground salinity of each of the two populations, or Atlantic salinity conditions resembling the phylogenetic origin of Clupea harengus . In addition, larvae were exposed to a Vibrio spp . infection. Life‐history traits and gene expression analysis served as response variables. Herring seem adapted to Baltic Sea conditions and cope better with low saline waters. However, upon a bacterial infection, herring larvae suffer more when kept at lower salinities implying reduced resistance against Vibrio or higher Vibrio virulence. In the context of recent climate change with less saline marine waters in the Baltic Sea, such interactions may constitute key future stressors.